“Biocontrol de moniliophthora roreriy phytophthora palmivora patógeno de cacao (theobroma cacao L.) con hongos endífitos procedentes del alto amazonas” - Rojas Torres, Marcelino (2013)
In arder to select endophytes fungal from Alto Amazonas with biocontrol ability to M. roreri and P. palmivora, pathogens of cacao (Theobroma cacao L.) and were selected at random 46 isolates belonging to 1 O genera ofendophytes fungal (Pestalotiopsis, Colletotrichum, Aspergillus, Penicillium, Fusarium, Trichoderma, Clonostachys, Botryosphaeria, Acremonium and Xylaria) to evaluate the antagonistic capacity and efficiency of endophytes, which was developed in Plant Pathology laboratory of Instituto de Cultivos Tropicales (ICT), located in the district of La Banda de Shilcayo, province and department of San Martín. For the test of Antibiosis were produced secondary metabolites of endophytes in MIN broth, and was evaluated the percentage of mycelial inhibition of pathogens, and to the test of mycoparasitism was used the method of plate pre-colonized by pathogens, and was assessed of colonization percentage. For testing the efficiency of biocontrol of M. roreri was used the cylinder method of cocoa fruit tissues infected with monilia, likewise, to test the efficiency of biocontrol of P. palmivora, the method of leaf discs. In the antibiosis test, secondary metabolites of isolation As-E-3 from genus Aspergillus, had greater effect on mycelial inhibiting of M. rorerí and P. palmívora with 95. 13% and 100% respectively. In testing of mycoparasitism to M. roreri five isolates belonging to Trichoderma resulted being aggressives mycoparasites that completely colonized the pathogen. However, the isolates of Aspergillus genera (As-E-6, As-E-5, As-E-3 AsE- 1 ), Botryosphaeria (ali isolates), Trichoderma (T-E-166, T-E-5) and Xylaria (X-E- 55) were the ones who preved to be very aggressive mycoparasite for P. palmívora. On the other hand, the efficiency of endophytes against M. roreri in presence of secondary metabolites, isolation P-E-168 (Pestalotiopsis) showed greater inhibition with 97.85%; while in the conidial suspension test showed that ali isolates of Trichoderma · had an antagonistic effect on the pathogen, exceeding 90% of sporulation inhibition. In tests of efficiency of secondary metabolites and conidial suspension in the control of P. palmivora in leaf discs, isolation As-E-3 of Aspergil/us showed greater antagonistic effect on infection of pathogens, and resulted smaller degree of severity of disease of 0.05 and 1.93 fer metabolites and suspension conidia respectively.